The Impact of Smart Home Technologies on Child Safety and Development - Javed Rahman; Omid Farid Khan (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
Smart home technologies, such as voice assistants, surveillance systems, and smart devices, are becoming increasingly common in households. This paper examines how these technologies can improve child safety by monitoring activities, alerting parents about potential hazards, and providing educational tools. It also explores the potential psychological and developmental effects of smart homes on children, including their impact on cognitive growth and independence.